Effect Of Seft Giving (Spiritual Emotional Freedom Technique) On The Level Of Anxiety Of Covid 19 Patients In The Edelweis Isolation,Orthopedic Hospital Prof. Dr. R. Soeharsosurakarta - Rochma, Erwi; Rohman, Rohman; Ansori, Wahid; Aiyanto, Ferry; Muthmainah, Qowiyatul; Dewi Suciningtyas, Putri (International Journal of Science, Technology & Management, 2023)
Coronavirus Disease (covid-19) is a disease caused by the Severe AcuteRespiratory Syndrome Coronavirus-2(SARS-COV-2) virus. Coronavirus Disease(covid-19) has become a worldwide pandemic. This study aims to determine theEffect of Giving SEFT (Spiritual Emotional Freedom Technique) Regarding the Anxiety Level of Covid-19 Patients in the Edelweis Isolation Ward, Prof. Orthopedic Hospital. Dr. R. Soeharso Surakarta. Thisresearch is a quantitativestudy, with the experimental method of one group pre and post test design (withoutcontrol group), which is done to reveal causal relationships or influences by involving one group of subjects.This research was conducted on 30 respondents in the Edelweis Isolation Ward, Prof. Orthopedic Hospital. Dr. R. Soeharso Surakarta, with female sex as much as 60% and the most age range 45-55 years asmuch as 36.7%, most jobs are private as much as 20% and most education is S1 as many as 33.3%. Respondents with comorbidities were 43.3% and 23.3% were patients with pneumonia. From the results of the analysis using the Wilcoxon test, the p-value = 0.00001 (<0.05). There is an effect of giving SEFT (Spiritual EmotionalFreedom Technique) therapy on the anxiety level of Covid-19 patients in the Edelweis ward of Prof.Orthopedic Hospital. Dr. R. Soeharso Surakarta.